Distributed Optimal Dispatch of Virtual Power Plant via Limited Communication - Yang, Hongming; Yi, Dexin; Zhao, Junhua; Dong, ZhaoYang (IEEE transactions on power systems, 2013)
In this letter, a distributed optimal dispatch method based on the distributed primal-dual sub-gradient algorithm is proposed. By coordinating individual decision-making of distributed energy resources (DERs) in the virtual power plant (VPP) via limited communication, the profit of VPP can be maximized. It can be proven that the proposed distributed algorithm has similar performance to the centralized dispatch.